Comparisons of traditional electrocardiographic criteria for left and right ventricular hypertrophy in young Asian women: The CHIEF heart study. Issue 42 (16th October 2020) - Su, Fang-Ying; Lin, Yen-Po; Lin, Felicia; Yu, Yun-Shun; Kwon, Younghoon; Lu, Henry Horng-Shing; Lin, Gen-Min
Abstract : Abstract: The performance of electrocardiographic (ECG) voltage criteria to identify left and right ventricular hypertrophy (LVH and RVH) in young Asian female adults have not been clarified so far. In a sample of 255 military young female adults, aged 25.2 years on average, echocardiographic LVH was respectively defined as the left ventricular mass (LVM) indexed by body surface area (BSA) (≥88 g/m 2 ) and by height 2.7 (≥41 g/m 2.7 ), and RVH was defined as anterior right ventricular wall thickness >5.2 mm. The performance of ECG voltage criteria for the echocardiographic LVH and RVH were assessed by area under curve (AUC) of receiver operating characteristic (ROC) curve to estimate sensitivity and specificity. For the Sokolow-Lyon (the maximum of SV1 or SV2 + RV5 or RV6 ) and Cornell (RaVL + SV3 ) voltage criteria with the LVM/BSA ≥88 g/m 2, the AUC of ROC curves were 0.66 (95% confidence intervals [CI]: 0.52–0.81, P = .039) and 0.61 (95% CI: 0.44–0.77, P = .18), respectively. For these 2 ECG voltage criteria with the LVM/height 2.7 ≥41 g/m 2.7, the AUC of ROC curves were 0.64 (95% CI: 0.52–0.75, P = 0.11) and 0.73 (95% CI: 0.61–0.85, P = 0.0074), respectively. The best cut-off points selected for the Sokolow-Lyon and Cornell voltage criteria with echocardiographic LVH in young Asian females were 26 mm and 6 mm, respectively. In contrast, all the AUC of ROC curves were less than 0.60 and not significant according to the Sokolow-Lyon (the maximum of RV1 + SV5 or V6) and Myers' voltage criteria (eg, the voltage of R wave in V1 and the ratios of R/S in V1, V5 and V6) with echocardiographic RVH. There was a suggestion that the ECG voltage criteria to screen the presence of LVH should be adjusted for the young Asian female adults, and with regard to RVH, the ECG voltage criteria were found ineffective.